KUALITAS APARATUR DALAM MENINGKATKAN PELAYANAN PUBLIK DI KANTOR LURAH PULUBAALA KECAMATAN KOTA TENGAH KOTA GORORNTALO - Franky Djafar; Djafar Amin; Usan Bagou (Universitas Muhammadiyah Gorontalo, 2013)
This study aimed to determine the quality of personnel in improving public services in the office of Chief of Gorontalo City Pulubala. This study uses secondary data sources such as library research and documentation, among others, can be obtained from the district office, the news media and the Internet, as well as other literature related to the problems studied, namely the quality of service of the government apparatus in an effort to serve the community and also using interviews with informants that village heads, village officials and the public. The data obtained from these studies were analyzed by descriptive qualitative analysis method. The indicators in this study, researchers used the first indicator of the sub-indicators Productivity Work Attitude and Ability Village officials conduct administrative personnel, adherence to regulatory authorities with an indicator procedure / service procedures, and discipline with the presence of sub-indicators of urban authorities and appropriate care Results with the wishes of the community in assessing service in urban pulubala. From the research and discussion about improving the quality of personnel in the public service in the office Chief Pulubala in Gorontalo City authors conclude that the administrative apparatus of the government was ready to face regional autonomy, as seen on the achievement of optimum quality pulubala administrative apparatus in improving public services.